The rhetorical structure and evaluative language of restaurant reviews in I.M. magazine / Nadiah Husna Zainuddin - Nadiah Husna , Zainuddin (2019)
The purpose of this research is to conduct a genre analysis on restaurant reviews from one particular print magazine, which is I.M. Magazine. The 18 restaurant reviews that were selected were analyzed using an adapted/analytical framework, combining two frameworks, Kathpalia’s (1992) framework as well as Hou’s (2012) Moves for Newspaper Restaurant Reviews in order to identify the rhetorical moves of the restaurant reviews. This study also looks into the linguistic features present in the reviews, specifically evaluative language, focusing on the use of certain lexico – grammatical features that are prominently used throughout the reviews. According to Moir (2007), restaurant reviews help determine dining decisions and restaurateurs believe that it may affect their sales both negatively and positively. From the analysis, it can be seen that the communicative purpose of restaurant reviews is informative in nature, as there are only a few promotional elements identified. Consequently, this research will hopefully garner more information that may be useful in ESP pedagogy for students to write effectively, and to the food and restaurant industries in general.